A new view of macula densa cell microanatomy - Gyarmati, Georgina; Shroff, Urvi Nikhil; Riquier-Brison, Anne; Kriz, Wilhelm; Kaissling, Brigitte; Neal, Christopher R.; Arkill, Kenton P.; Ahmadi, Nariman; Gill, Inderbir S.; Moon, Ju-Young; Desposito, Dorinne; Peti-Peterdi, János (American journal of physiology. Renal physiology, 2021)
Download figureDownload PowerPoint